The life and work of H. Jones Thaddeus 1859-1929 - Rooney, Brendan (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2000)
The early chapters of this thesis cover Harry Jones Thaddeus’s formative years, including his youth in Cork, where he attended and excelled at the Cork School of Art, and received his first commissions, the important period he spent at Heatherley’s studio in London, and his extremely influential sojourn at the Academic Julian, in Paris. These chapters focus particularly on the nature of the training he received in these institutions, and on the social factors than shaped his life there. Leaving Paris, Thaddeus was afforded his first real artistic independence in Brittany, where he joined artists from all over Europe and America in the artist colony of Concameau, and displayed an ambition and application which was to characterise most of his career. The technical competence and confidence that he had developed in these early years found full expression when he settled in Florence, and began making inroads, both social and professional, into the city’s expatriate elevated society. Thaddeus’s experience there and exposure to the lucrative potential of society portraiture proved hugely significant in determining the course that his career took subsequently, and are analysed in detail.
Keywords: History of Art and Architecture, Ph.D.; Ph.D. Trinity College Dublin